Microwave sintering of dense and lattice 3Y-TZP samples shaped by digital light processing. Issue 5 (1st March 2023) - Khalile, Nouhaila; Meunier, Christophe; Petit, Clémence; Valdivieso, François; Coppola, Bartolomeo; Palmero, Paola
Abstract: Nowadays it is possible to produce ceramic parts with solid and complex shapes with rapid and efficient shaping and sintering techniques. In this paper, 3mol% yttria stabilized zirconia (3Y-TZP) dense and lattice parts were shaped by Digital light processing method (DLP) and densified by conventional (CV) and microwave (MW) sintering. 3Y-TZP samples were MW sintered up to 1550 °C with different heating rates (10, 30, and 50 °C/min) for the dense samples and 30 °C/min for the lattice samples. Controlled thermal cycles with a homogenous heating and no thermal runaway was reached. CV sintering was carried out at 10 °C/min up to 1550 °C. No inter-layer delamination was detected after sintering by the two methods. Both dense and lattice MW-sintered samples reached high final densities (equivalent to obtained values with CV-sintered samples, i.e., ≥98% T.D.), but exhibited a lower average grain size than CV-sintered materials. The different architectures between dense and lattice samples resulted in a different specific absorbed power: the power absorbed by the dense sample is lower than that absorbed by the lattice one meaning that this sample architecture heats up easily.